2008
DOI: 10.1124/mol.107.038323
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Targeting the Adenine- and Uracil-Rich Element of bcl-2 mRNA with Oligoribonucleotides on Apoptosis, Cell Cycle, and Neuronal Differentiation in SHSY-5Y Cells

Abstract: We have identified previously a destabilizing adenine-and uracilrich element (ARE) in the 3Ј-UTR of bcl-2 mRNA that interacted with ARE-binding proteins to down-regulate bcl-2 gene expression in response to apoptotic stimuli. We have also described three contiguous 2Ј-O-methyl oligoribonucleotides (ORNs) in both sense and antisense orientation with respect to the bcl-2 ARE that are able to regulate the bcl-2 mRNA half-life and Bcl-2 protein level in two different cell lines. Here we show that treatment of neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…The pathogenesis of a wide variety of human diseases is frequently related to impaired control of apoptosis [28]. Indeed, we observed that Bcl-2 expression was high in neuroblastic tumors, but Bax expression was relatively low or undetectable.…”
Section: Discussionmentioning
confidence: 66%
“…The pathogenesis of a wide variety of human diseases is frequently related to impaired control of apoptosis [28]. Indeed, we observed that Bcl-2 expression was high in neuroblastic tumors, but Bax expression was relatively low or undetectable.…”
Section: Discussionmentioning
confidence: 66%
“…Furthermore, Bcl-2 ORNs stabilized other ARE containing transcripts and up regulated their expression. We also demonstrated that treatment of the SHSY-5Y neuronal cells with Bcl-2 ORNs prevented Bcl-2 down-regulation in response to apoptotic stimuli, such as glucose/growth factor starvation or oxygen deprivation, inhibited cell cycle entry and induced a markedly increase of cellular neurite number and length, a hallmark of neuronal differentiation resulting from Bcl-2 up-regulation [46] . Enhancement of apoptotic threshold and induction neuronal differentiation by Bcl-2 ORNs suggested evaluating their potential application to prevent pathological apoptosis and neuronal degenerations.…”
mentioning
confidence: 71%
“…Nonetheless, even higher benefits, mainly in term of potency, may be provided by the ASO strategy. In this respect, we have extensively applied this strategy to inhibit the expression of several genes, also in therapeutic settings [21,[25][26][27]. In addition, ASOs have been specifically applied for the treatment of eye diseases including cytomegalovirus retinitis, keratitis-induced corneal neovascularization and inherited retinal diseases [35].…”
Section: Discussionmentioning
confidence: 99%
“…More than twenty years ago, for the first time we strongly inhibited uPAR expression at the level of its mRNA in cultures of human fibroblasts using a specific ASO (ASO-uPAR) [24]. Having continuously updated our skills on ASO strategies aimed at modulating gene expression in different experimental models [21,[25][26][27], in the present study we explored the effectiveness of ASO-uPAR in inhibiting angiogenic responses both in vitro and in vivo. Therefore, we investigated the ASO-…”
Section: Introductionmentioning
confidence: 99%